Critical success factors for the internationalisation of small-medium enterprises in Indonesia - Sofik Handoyo; Ivan Yudianto; Fury Khristianty Fitriyah (Cogent Business & Management, 2021)
The purpose of this study was to identify critical success factors (CSFs) for Indonesian small-medium enterprises (SMEs) accessing international markets. The study used the resource-based view, the knowledge-based view, and network theory as a theoretical framework to assess CSFs. The population consisted of Indonesian exporting SMEs registered with the Indonesian Ministry of Cooperatives and Small Businesses. The total sample contained 153 SME exporters, which were selected using convenience sampling techniques. Paper-based and electronic questionnaire instruments were used to collect the data. The questionnaires were distributed through small-medium enterprises' export networks and to SME respondents at an international trade exhibition. Factor analyses, namely exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), were applied. The research findings revealed that international market knowledge, product innovation knowledge, and institutional networking are critical success factors for the internationalisation of small-medium enterprises in Indonesia. The study contributes by enriching the body of knowledge regarding firm internationalisation theory and providing valuable information for understanding small-medium enterprises' internationalisation in an emerging country such as Indonesia.
Keywords: 650; Small-medium enterprises; resource-based view; knowledge-based view; network theory; convenience sampling; internationalisation